2010
DOI: 10.7589/0090-3558-46.1.316
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to Selected Viral and Bacterial Pathogens in Wild Boar (Sus scrofa) in Campania Region, Italy

Abstract: Serum samples were collected from wild boars (Sus scrofa) harvested during the 2005-2006 hunting season in Campania, southern Italy. Samples were tested for antibodies to Leptospira interrogan, Brucella spp., Salmonella spp., Aujeszky disease virus (ADV), porcine reproductive and respiratory stress syndrome virus (PRRSV), porcine parvovirus (PPV), classical swine fever virus (CSFV), and swine vesicular disease virus (SVDV). Of the 342 serum samples tested, 15 (4.4%) were seropositive to Brucella spp., nine (2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
59
3
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 13 publications
13
59
3
8
Order By: Relevance
“…The wild boar is currently the most widely dispersed ungulate in Italy, with a range encompassing 190,000 km 2 , or 64% of the area of the country (Carnevali et al, 2009). Because wild boars often share habitat with domestic animals, they can act as a potential source of infectious diseases, especially for domestic pigs, and interactions between these two populations can amplify the spread of infectious agents (Montagnaro et al, 2010). Previous surveys in Germany (Hotzel et al, 2004) and Spain (Salinas et al, 2009) suggested the potential role of the wild boar as a wildlife reservoir for the same Chlamydiaceae species detected in the domestic pig, including Chlamydia suis, Chlamydophila pecorum, Chlamydophila abortus, and Chlamydophila psittaci.…”
mentioning
confidence: 99%
“…The wild boar is currently the most widely dispersed ungulate in Italy, with a range encompassing 190,000 km 2 , or 64% of the area of the country (Carnevali et al, 2009). Because wild boars often share habitat with domestic animals, they can act as a potential source of infectious diseases, especially for domestic pigs, and interactions between these two populations can amplify the spread of infectious agents (Montagnaro et al, 2010). Previous surveys in Germany (Hotzel et al, 2004) and Spain (Salinas et al, 2009) suggested the potential role of the wild boar as a wildlife reservoir for the same Chlamydiaceae species detected in the domestic pig, including Chlamydia suis, Chlamydophila pecorum, Chlamydophila abortus, and Chlamydophila psittaci.…”
mentioning
confidence: 99%
“…Available scientific publications provide not much information about persistence of PRRSV in wild boars. PRRSV antibodies in wild boars have been only discovered in a few countries and only in some individual cases (2,17,18,22). At present, it is thought domestic pigs can infect wild boars with PRRSV rather than vice versa; however, an evidence is still lacking and opinions are often contradictory.…”
Section: Introductionmentioning
confidence: 95%
“…Estudios similares hechos en diferentes países han mostrado niveles de prevalencia diferentes. Vicente et al señalan una prevalencia de 12 % para L. pomona en cerdos en España, mientras que Montagnaro et al analizaron 342 muestras de suero de cerdos en Italia y obtuvieron solo 2.6 % de positividad para las serovariedades de L. copenagheni, L. bratislava y tarassovi 27,29 . Estos y otros estudios solo se enfocan en una o tres serovariedades, mientras que nosotros evaluamos nueve.…”
Section: Leptospirosisunclassified
“…en 61 de 70 cerdos (87.14 %). Estos valores de seroprevalencia rebasan a los reportados en poblaciones silvestres de cerdos en Italia (19.3 %) 29 , España (4 %) 27 y Estados Unidos de América (5 %) 30 . De igual forma, en Eslovenia, en un estudio Artículo Científico…”
Section: Salmonelosisunclassified
See 1 more Smart Citation